
求证:(1-sinα+cosα)/(1+sinα+cosα)=tan(π/4-α/2)
1个回答
展开全部
证明:
(1-sinα+cosα)/(1+sinα+cosα)
=[sin^2(a/2)+cos^2(a/2)-2sina/2cosa/2+cos^2(a/2)-sin^2(a/2)]/[sin^2(a/2)+cos^2(a/2)+2sina/2cosa//2+cos^2(a/2)-sin^2(a/2)]
=[2cos^2(a/2)-2sina/2cosa/2]/[2cos^2(a/2)+2sina/2cosa/2]
=2cosa/2(cosa/2-sina/2)/[2cosa/2(cosa/2+sina/2)]
=(cosa/2-sina/2)/(cosa/2+sina/2)
=√2sin(π/4-a/2)/[√2cos(π/4-a/2)]
=sin(π/4-a/2)/cos(π/4-a/2)
=tan(π/4-α/2)
(1-sinα+cosα)/(1+sinα+cosα)
=[sin^2(a/2)+cos^2(a/2)-2sina/2cosa/2+cos^2(a/2)-sin^2(a/2)]/[sin^2(a/2)+cos^2(a/2)+2sina/2cosa//2+cos^2(a/2)-sin^2(a/2)]
=[2cos^2(a/2)-2sina/2cosa/2]/[2cos^2(a/2)+2sina/2cosa/2]
=2cosa/2(cosa/2-sina/2)/[2cosa/2(cosa/2+sina/2)]
=(cosa/2-sina/2)/(cosa/2+sina/2)
=√2sin(π/4-a/2)/[√2cos(π/4-a/2)]
=sin(π/4-a/2)/cos(π/4-a/2)
=tan(π/4-α/2)
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询